Developing a Framework for Addressing Research Competence and Challenges Among Local College Faculty: Toward a Targeted Training Program - Quiño-Justol, Jeddah; Gomez, Frederick (Journal of Interdisciplinary Perspectives, 2025)
Improving the research competencies of faculty remains a significant challenge for higher education institutions (HEIs) in the Philippines, with low research productivity often linked to limited faculty competencies. This study assessed the faculty's research competencies and challenges at a Local College in Tagoloan, Misamis Oriental, Philippines, to address these gaps and propose solutions. Using an explanatory sequential mixed-method design, the researchers combined quantitative data from a Research Competencies Scale with qualitative insights from open-ended questions. The study evaluated research competencies across six domains: research inquiry, literature review, sampling methods, qualitative and quantitative processes, ethics, and dissemination. Results indicated moderate overall competency, with strengths in theoretical frameworks and ethical standards but significant challenges in formulating qualitative research questions and adhering to scholarly writing standards. Time management, resource limitations, and gaps in foundational skills emerged as significant barriers, compounded by a lack of institutional support and mentorship. The study proposed a structured training program based on the S-P-A-T (Strategy, Program, Activities, Tasks) framework to address these issues. Key recommendations included establishing an Education Research and Development Office with an accompanying Research Ethics Board, allocating 1% of the institutional budget for research initiatives, and implementing interactive workshops to enhance research design, data analysis, and scholarly writing skills. By leveraging existing resources and addressing systemic barriers, the institution can foster a robust research culture and empower faculty to make meaningful academic and community development contributions. This study highlights the importance of institutional support, targeted training, and collaboration in aligning faculty research competencies with higher education goals and national priorities.